Heterogeneous Networking in C-ITS - Martin Srotyr (Journal of Systemics, Cybernetics and Informatics, 2017)

(untitled)
Cooperative Systems are part of the Smart Cities solutions and the essential part of the cooperative systems represents guaranteed quality of information exchange both between VANET members (V2V) as well as between VANET and Infrastructure (V2I). This article presents proposal of multiplatform routing protocol designed for combination of two most widely accepted mobile technologies. Properties of proposed protocol are in VANET communication simulation compared with selection of mostl